2014
DOI: 10.1128/jcm.01127-14
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis B Virus Genotypic Resistance Mutations by Coamplification at Lower Denaturation Temperature-PCR Coupled with Sanger Sequencing

Abstract: Mutations in the reverse transcriptase (rt) region of the DNA polymerase gene are the primary cause of hepatitis B virus (HBV) drug resistance. In this study, we established a novel method that couples coamplification at lower denaturation temperature (COLD)-PCR and Sanger sequencing, and we applied it to the detection of known and unknown HBV mutations. Primers were designed based on the common mutations in the HBV rt sequence at positions 180 to 215. The critical denaturation temperature (T c ) was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In this study, except rtA181T, the classical primary drug resistance mutations (i.e., I169T, A181T/V, T184A/C/F/G/I/L/M/S, A194T, S202C/G/I, M204I/V/S, N236T, and M250I/L/V) were not detected by Sanger sequencing in treatment-naive patients (Table 3), which was consistent with previous reports (6, 25, 26). Considering that Sanger sequencing is a population-based sequencing approach used to detect mutations with an intrahost rate of more than 20% (6, 27), the minor mutations with an intrahost rate of less than 20% were likely to be ignored by Sanger sequencing. In this study, using next-generation sequencing, mutations were found at rt202 (rtS202R/I/N/C/G), rt204 (rtM204L/R/I), rt236 (rtN236T/K/H), and rt250 (rtM250I/L) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, except rtA181T, the classical primary drug resistance mutations (i.e., I169T, A181T/V, T184A/C/F/G/I/L/M/S, A194T, S202C/G/I, M204I/V/S, N236T, and M250I/L/V) were not detected by Sanger sequencing in treatment-naive patients (Table 3), which was consistent with previous reports (6, 25, 26). Considering that Sanger sequencing is a population-based sequencing approach used to detect mutations with an intrahost rate of more than 20% (6, 27), the minor mutations with an intrahost rate of less than 20% were likely to be ignored by Sanger sequencing. In this study, using next-generation sequencing, mutations were found at rt202 (rtS202R/I/N/C/G), rt204 (rtM204L/R/I), rt236 (rtN236T/K/H), and rt250 (rtM250I/L) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…With the design of COLD-PCR for the amplification of P1 and P2 fragments, corresponding to the B, C, D, and E domains in HBV RT, the developed method can be applied for sensitive detection of major NA-drug resistance mutations, including three mt (rtV173L, rtL180M, and rtM204I/V) that are associated not only with LMV and ETV resistance but also with vaccine escape [ 12 , 14 ]. Additional mt including rtS256G for resistance to LMV and rtL229V, rtI233V, rtP237T, and rtN238A/K/T for resistance to ADF were detected based on the work of Liu and his colleagues [ 21 ]. To confirm the reliability of mt detection in clinical samples by the COLD-PCR method, we cross-checked the two representative samples having the lowest mt peaks constituting ≤20% of the wt peak heights based on real-time PCR assay using Taqman LNA probes.…”
Section: Discussionmentioning
confidence: 99%
“…The size of P1 and P2 fragments were intentionally designed to be <200 nt, as recommended previously [ 21 , 22 ], to ensure the difference in melting temperature between homoduplex (mt-mt; wt-wt) and heteroduplex (mt-wt).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the denaturation temperature of the mutant DNA is often lower than that of wild type DNA. The assay is often used for viral gene mutation [59] detection, cancer associated gene mutations (p53) [60,61], EGFR, KRAS, etc. ), beta globulin (HBB) mutations that cause beta thalassemia [62], etc.…”
Section: Cold-pcrmentioning
confidence: 99%